Assessing the effect of a laundry detergent ingredient (LAS) on organisms of a rural South African river - Gordon, Andrew K (Rhodes University, Faculty of Science, Institute for Water Research, 2012)
Powdered laundry detergents are consumed in high volumes worldwide. Post use, they are directed toward water resources via wastewater treatment works or, as is the situation in many rural areas of South Africa, they enter the environment directly as a result of laundry washing activity undertaken alongside surface waters. Within wastewater treatment works, the main ingredient in powdered laundry detergents, the narcotic toxin linear alkylbenzene sulfonate (LAS), is mostly removed, rendering the waste stream a negligible risk to the aquatic biota of receiving waters. In contrast, the biological and ecological impacts of direct LAS input to the aquatic environment, as a consequence of near-stream laundry washing, are yet to be fully realised. Consequently, this thesis posed two research questions: 1) 'What are the LAS concentrations in a small rural South African river'? and 2) 'Is the in-stream biological community negatively affected at these concentrations?' The chosen study area, the community of Balfour in the Eastern Cape Province, is like many rural areas of South Africa where inadequate provision of piped water to homesteads necessitates laundry washing alongside the nearby Balfour River. The first research question was addressed in two ways: by predicting LAS concentrations in Balfour River water by assessing detergent consumption and laundry washing behaviour of residents living alongside the river; and measuring actual in- stream LAS concentrations on different days of the week and during different seasons. Results indicated that LAS concentrations were highly variable temporally and spatially. High peak concentrations of LAS occurred infrequently and were limited to the immediate vicinity of near-stream laundry washing activity with the highest measured concentration being 342 Î¼g.L â »Â¹ and the average 21 Î¼g.L â »Â¹ over the sampling period. The second research question was addressed by integrating the chemical evidence, determined from the first research question, with the biological evidence of stress responses measured in macroinvertebrates collected downstream of near-stream laundry washing activity on the Balfour River. Predicted and measured LAS exposure concentrations from the Balfour River were compared to a water quality guideline for LAS (304 Î¼g.L â »Â¹), specifically derived in this thesis. Biological stress responses were measured at different levels of organisation: two sub-cellular responses (lipid peroxidation and cholinesterase activity); three measures of macroinvertebrate tolerance to water quality impairment; five measures of community composition; three measures of community richness; and a surrogate measure of ecosystem function (functional feeding groups). Weight-of-evidence methodology was utilised to assess, integrate and interpret the chemical and biological evidence, and at its conclusion, determined no effect on the in-stream biological community of the Balfour River downstream of laundry washing activity.
Keywords: Detergent pollution of rivers, lakes, etc. -- Research -- South Africa -- Eastern Cape; Water -- Pollution -- Research -- South Africa -- Eastern Cape; Stream health -- Research -- South Africa -- Eastern Cape; Stream ecology -- Research -- South Africa -- Eastern Cape